PERAN MOTIVASI DAN DISIPLIN KERJA DALAM MENINGKATKAN KINERJA APARATUR SIPIL NEGARA PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA PROVINSI NUSA TENGGARA TIMUR - Marselinda Hege; Yusniaty Kore Naha; Jhon S. Liem (P3M Politeknik Negeri Ambon, 2026)
This study aims to examine the role of work motivation and work discipline in improving the performance of Civil Servants (ASN) at the Department of Community and Village Empowerment of East Nusa Tenggara Province. A quantitative research approach with a survey method was employed. The study involved 50 Civil Servants selected using a simple random sampling technique. Primary data were collected through questionnaires based on a five-point Likert scale, while supporting information was obtained through observation, interviews, and documentation. The collected data were analyzed using multiple linear regression, followed by partial (t-test), simultaneous (F-test), and coefficient of determination (R²) analyses to examine the relationships among the research variables. The findings indicate that work motivation has a positive and significant effect on employee performance. Likewise, work discipline also has a positive and significant effect on employee performance. Simultaneously, work motivation and work discipline significantly influence employee performance, indicating that both variables contribute substantially to improving the performance of Civil Servants. The study concludes that enhancing employee motivation and strengthening work discipline are essential strategies for improving organizational performance and delivering more effective and efficient public services. Keywords: work motivation; work discipline; employee performance.